Mutant Prpf31 causes pre-mRNA splicing defects and rod photoreceptor cell degeneration in a zebrafish model for Retinitis pigmentosa - Yin, Jun; Brocher, Jan; Fischer, Utz; Winkler, Christoph (Molecular neurodegeneration, 2011)
Retinitis pigmentosa (RP) is an inherited eye disease characterized by the progressive degeneration of rod photoreceptor cells. Mutations in pre-mRNA splicing factors including PRPF31 have been identified as cause for RP, raising the question how mutations in general factors lead to tissue specific defects.